The whip hand - Maxwell, Douglas, 1974- (Oberon modern plays., 2017)
It's Dougie's birthday. He just turned 50 and his family are throwing him a party. But it's he who has a surprise for them. A bombshell proposal. He wants his ex-wife Arlene to back his new endeavour. He wants to serve a good cause, a global cause. He wants to make right a terrible wrong, even if it puts their daughter's future at risk. They can all sense a scam, but Dougie won't back down. He is convinced this is his only chance to do something truly glorious, but his motivation may not be as pure as it seems. As the touchpaper under his family is lit, no one escapes the fallout. The Whip Hand is an explosive new play about power, privilege, blood ties and our inescapable past.